REPRESENTASI KEPEMIMPINAN PATIH GAJAH MADA DALAM MEMIMPIN PASUKAN BHAYANGKARA MELALUI KARYA TARI “TANDYA” MENGGUNAKAN METHODS of CONSTRUCTION JACQUELINE MARY SMITH-AUTARD - Mustika, Nimas Cahyani (Program Studi Pendidikan Tari FBS UNJ, 2020)
The purpose of the Dance Works aimed to Representation the Leadership of Patih Gajah Mada in Leading the Bhayangkara force into the form of TANDYA dance works.This dance work entitled